2005
DOI: 10.1210/me.2004-0537
|View full text |Cite
|
Sign up to set email alerts
|

The Ligand-Dependent Interaction of Mineralocorticoid Receptor with Coactivator and Corepressor Peptides Suggests Multiple Activation Mechanisms

Abstract: We investigated the coregulator (coactivator and corepressor) interactions with the mineralocorticoid receptor (MR) that lead to activation and inhibition of the receptor in the presence of agonist and/or antagonist. Our results indicate that MR ligand binding domain (LBD) interacts strongly with only a few specific coactivator peptides in the presence of the agonist aldosterone and that these interactions are blocked by the antagonist eplerenone. We also discovered that cortisol, the preferred physiological l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 46 publications
3
64
0
Order By: Relevance
“…These results suggest that Ubc9 contributes to MR-dependent transcriptional activation at least partly by binding SRC-1 and recruiting it to cellular transcriptional machinery. Because recent reports (56) showed that relatively few coactivators, including SRC-1, strongly interact with MR in the presence of aldosterone, these findings are consistent with our data that Ubc9 and SRC-1 cooperatively function as coactivators of MR.…”
Section: Endogenous Ubc9 Is Required For Mr-mediated Transactivation-ifsupporting
confidence: 93%
“…These results suggest that Ubc9 contributes to MR-dependent transcriptional activation at least partly by binding SRC-1 and recruiting it to cellular transcriptional machinery. Because recent reports (56) showed that relatively few coactivators, including SRC-1, strongly interact with MR in the presence of aldosterone, these findings are consistent with our data that Ubc9 and SRC-1 cooperatively function as coactivators of MR.…”
Section: Endogenous Ubc9 Is Required For Mr-mediated Transactivation-ifsupporting
confidence: 93%
“…20 Specific mutations in the MR-LBD can also dissociate the effects of aldosterone and cortisol on coactivator interactions. 25 These observations together with studies of other steroid receptors indicate an unexpected degree of plasticity in the receptor allowing the conformation to be in part dictated by the ligand.…”
Section: Mineralocorticoid Receptormentioning
confidence: 93%
“…Figure 5 also shows the α-helices on the MR as determined by X-ray crystallography (Bledsoe et al 2005, Fagart et al 2005, Edman et al 2015 and amino acids that have been found to be important in either steroid binding or transcriptional activation of the MR or CR (Fagart et al 1998, Geller et al 2000, Bledsoe et al 2005, Hultman et al 2005, Bridgham et al 2006, Shibata et al 2013, Edman et al 2015, Jimenez-Canino et al 2016, Mani et al 2016 or the GR (Bledsoe et al 2002, He et al 2014, Edman et al 2015, Mani et al 2016. A striking feature, discussed in more detail below, is the strong conservation of amino acids among the CR, MR, GR, PR and AR, including lamprey PR and CR.…”
Section: Lldsmhdlvsdllefcfytfreshalkvefpamlveiisdqlpkvesgnakplyfhrkmentioning
confidence: 97%
“…9). Differences in the conformation of AF2 may be important in selective binding of coactivators to MR and GR (Hultman et al 2005, Hu & Funder 2006, Baker et al 2007, Yang & Young 2009, Fuller et al 2012, Baker et al 2013). …”
Section: Function Of Ser-849 In Human Mr and Its Deletion In Tetrapodmentioning
confidence: 99%